Observasi Osilasi Resonansi Atmosfer di Ionosfer Setelah Erupsi Gunung Lewotobi Laki-laki Tahun 2025 Menggunakan GNSS-TEC - Rahayu, Ririn Wuri; Susilowati (Program Studi Teknik Geomatika Fakultas Teknologi Mineral Universitas Pembangunan Nasional, 2025)
Volcanic eruptions can generate atmospheric acoustic and gravity waves that propagate upward and induce oscillations in the ionosphere. These disturbances can be detected through variations in the Total Electron Content (TEC) derived from Global Navigation Satellite System (GNSS) observations. In this study, we analyze ionospheric responses following the 2025 eruption of Mount Lewotobi Laki-laki, Indonesia, using GNSS-TEC data from nearby CORS stations. The analysis focuses on slant TEC variations associated with multiple GNSS satellites, revealing a distinct oscillatory pattern observed prominently on GLONASS satellite R42. After applying a high-pass filter to remove long-term trends, the residual TEC time series exhibited monochromatic oscillations with periods of approximately 3–5 minutes, consistent with the Type-1 (continuous) ionospheric disturbance described by Heki and Fujimoto (2022). Spectral analysis using the Blackman–Tukey method showed dominant frequency components near 3.7–5.4 mHz, corresponding to the acoustic resonance frequencies of the atmosphere. These findings provide evidence of atmospheric resonance oscillations in the ionosphere triggered by the Lewotobi Laki-laki eruption, demonstrating the potential of GNSS-TEC observations for monitoring ionospheric signatures of volcanic activity in Indonesia.